Associations Between Antithrombosis and Ventilator-Associated Events, ICU Stays, and Mortality Among Mechanically Ventilated Patients: A Registry-Based Cohort Study - Wang, Mingqi; Wang, Wen; Jia, Xue; He, Qiao; Zhu, Shichao; Kang, Yan; Zhang, Rui; Ren, Yan; Li, Ling; Zou, Kang; Zong, Zhiyong; Sun, Xin (Frontiers in Pharmacology, 2022)
Background: The effect of thromboembolism prophylaxis on clinical outcomes, such as ventilator-associated events (VAEs), ICU stays and mortality remains controversial. This study was conducted to evaluate the effect of pharmacological thromboprophylaxis on VAEs, ICU stays and ICU mortality among patients receiving mechanical ventilation (MV). Materials and Methods: A retrospective cohort study was conducted based on a well-established registry of healthcare-associated infections at ICUs in West China Hospital system. Patients who consistently received MV for at least 4 days from April 1, 2015 to December 31, 2018 were included. Hazard ratios (HRs) were compared for three tiers of VAEs, ICU stays and ICU mortality among patients receiving pharmacological thromboprophylaxis versus those without using time-dependent Cox model. For the analyses of ICU stays and ICU mortality, we also used Fine-Gray models to disentangle the competing risks and outcomes of interest. Results: Overall, 6,140 patients were included. Of these, 3,805 received at least one prescription of antithrombosis agents. Treatments with antithrombosis agents were associated with lower risk of VAEs (HR: 0.87, 95% CI: 0.77, 0.98) and ICU mortality (HR: 0.72, 95% CI: 0.61, 0.86) than those without. Anticoagulants but not antiplatelet agents were associated with decreased risk of VAEs (HR: 0.86, 95% CI: 0.75, 0.98), ICU mortality (HR: 0.62, 95% CI: 0.51, 0.76) and less time to ICU discharge (HR: 1.15, 95% CI: 1.04, 1.28). Antithrombotic may be associated with decreased risk of VAEs in patients with D-dimer > 5 mg/LFEU (HR: 0.84, 95%CI: 0.72, 0.98). Conclusions: Pharmacological thromboprophylaxis was associated with lower risk of VAEs and ICU mortality. Similar effects were observed between unfractionated heparins versus low-molecular-weight heparins.